2018
DOI: 10.1021/acsnano.8b03424
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Synthesized High-Mobility Tellurium Nanoflakes for Short-Wave Infrared Photodetectors

Abstract: Two-dimensional (2D) materials, particularly black phosphorus (bP), have demonstrated themselves to be excellent candidates for high-performance infrared photodetectors and transistors. However, high-quality bP can be obtained only via mechanical exfoliation from high-temperature- and high-pressure-grown bulk crystals and degrades rapidly when exposed to ambient conditions. Here, we report solution-synthesized and air-stable quasi-2D tellurium (Te) nanoflakes for short-wave infrared (SWIR) photodetectors. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
428
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(446 citation statements)
references
References 42 publications
18
428
0
Order By: Relevance
“…Interestingly, a 18.8-nm-thick 2D Te-based PD showed isotropic and anisotropic responsivity at wavelengths of 1.5 and 3 μm, respectively. It is indicated that the high anisotropy of the indirect bandgap was achieved for 2D Te nanosheet, while the direct bandgap was independent of the polarization of the infrared light [132]. Distinctly, Te also possesses an obvious photothermal effect in a wide broadband spectrum because of its narrow bandgap, which is already used in photothermal cancer therapy [159].…”
Section: Telluriummentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a 18.8-nm-thick 2D Te-based PD showed isotropic and anisotropic responsivity at wavelengths of 1.5 and 3 μm, respectively. It is indicated that the high anisotropy of the indirect bandgap was achieved for 2D Te nanosheet, while the direct bandgap was independent of the polarization of the infrared light [132]. Distinctly, Te also possesses an obvious photothermal effect in a wide broadband spectrum because of its narrow bandgap, which is already used in photothermal cancer therapy [159].…”
Section: Telluriummentioning
confidence: 99%
“…Therefore, Raman spectrum is a highly reliable technology to confirm the thickness range and chiralchain structure of Te. In view of the 1D helical chain along the c-axis and vdWs-like between chains in the triangular structure, 2D Te nanosheets exhibit unique anisotropy in bandgap, carrier mobility, phonon vibrations and optical absorption in the infrared region [132,147,154]. The angleresolved Raman peak intensities of different modes were observed in 13.5-nm Te nanosheets.…”
Section: Telluriummentioning
confidence: 99%
See 1 more Smart Citation
“…Data from refs. . d) Plot of the specific detectivity D * of various photodetectors versus detected wavelength.…”
Section: Photonic and Optoelectronic Applicationsmentioning
confidence: 99%
“…Data from refs. . e) Integration schemes for 2D‐material‐based saturable absorbers, showing: i) a schematic of black phosphorus coated fiber end and ii) its assembly into the photonic circuit through an adapter.…”
Section: Photonic and Optoelectronic Applicationsmentioning
confidence: 99%